A Systematic Literature Review of Peer-to-Peer, Community Self-Consumption, and Transactive Energy Market Models - Capper, Timothy (2022)
Capper, T., Gorbatcheva, A., Mustafa, M. A., Bahloul, M., Schwidtal, J. M., Chitchyan, R., Andoni, M., Robu, V., Montakhabi, M., Scott, I., Francis, C., Mbavarira, T., Espana, J. M., & Kiesling, L. (2021). A Systematic Literature Review of Peer-to-Peer, Community Self-Consumption, and Transactive Energy Market Models. Social Science Research Network (SSRN), Elsevier. https://doi.org/10.2139/ssrn.3959620